1993
DOI: 10.2307/3578394
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation Increases hsp-70 in Chinese Hamster Ovary Cells

Abstract: The induction of hsp-70 by gamma irradiation was studied in Chinese hamster ovary (CHO) cells. Synthesis of hsp-70 was assessed by SDS-PAGE of radiolabeled proteins while levels of hsp-70 mRNA were estimated by Northern blot analysis of total RNA. SDS-PAGE analysis indicated that the synthesis of hsp-70 was enhanced in cells exposed to 400 or 1000 Gy. Northern blot analysis of RNA from cells exposed to 1000 Gy indicated a rapid increase in mRNA capable of hybridizing to an hsp-70 oligonucleotide probe. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…Verbenko and Kalinin (1995) showed that several Hsps were induced by gamma rays in E. coli K-12 in which the SOS responses are constitutively expressed, and an interaction of the two stress systems in bacterial cells is possible. In addition, DnaK has been reported to be induced by gamma rays in eukaryotic cells (Sierra-Rivera et al 1993) to induce radioresistance (Park et al 2000) and to prevent radiation-induced cell death (Lee et al 2001). According to Calini et al (2003), DnaK overexpression acts as a radioprotective mechanism towards the first event of DNA damage and increases long-term viability.…”
Section: Discussionmentioning
confidence: 99%
“…Verbenko and Kalinin (1995) showed that several Hsps were induced by gamma rays in E. coli K-12 in which the SOS responses are constitutively expressed, and an interaction of the two stress systems in bacterial cells is possible. In addition, DnaK has been reported to be induced by gamma rays in eukaryotic cells (Sierra-Rivera et al 1993) to induce radioresistance (Park et al 2000) and to prevent radiation-induced cell death (Lee et al 2001). According to Calini et al (2003), DnaK overexpression acts as a radioprotective mechanism towards the first event of DNA damage and increases long-term viability.…”
Section: Discussionmentioning
confidence: 99%
“…20 Also, radiation has been found to affect cytosolic Hsp70 levels in tumor cells. [21][22][23] Since g-irradiation is frequently used in cancer therapy, 24,25 it is important to understand the molecular nature of radiation-induced effects on resistance of tumor cells to apoptosis. 26,27 Therefore, we investigated radiation-induced effects in three independent carcinoma cell systems that differ with respect to their capacity to express Hsp70 on their cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript proteins 15 . Less well known is the fact that major surgery can also have an immunosuppressive effect that leads to a significant diminution of lymphocyte and natural killer (NK) cell function 16 .…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%